ANALISIS PRAKTEK PENJUALAN PARA PEDAGANG SEMBAKO MUSLIM DALAMPERSPEKTIF ETIKA BISNIS ISLAM (STUDI KASUS PEDAGANG MUSLIM SEMBAKO DI PASAR TRADISIONAL AMBARKETAWANG, GAMPING KABUPATEN SLEMAN) - Abd Adim; Abdul Salam (LAN TABUR: Jurnal Ekonomi Syariah The Islamic University of KH. Achmad Muzakki Syah Jember, East Java. Jember Jln. Manggar Gebang Poreng 139A Patrang Jember Jawa Timur, 2021)
Islam was taught that economic activities cannot be separated from the basic values setout in the Qur'an, the hadith of the Prophet and other sources of Islamic teachings, as inconventional economics, Islamic economic systems also talk about human activities to obtainand regulate material or non-material assets in order to meet the necessities of life as humanbeings both individually and collectively concerning the acquisition, distribution (trade) or useto fulfill living needs. It can be seen the Islamic economic system in Ambarketawang Traditional Market, Sleman Regency, where the majority of traders are Muslim.